Pengaruh Profitabilitas, Likuiditas, dan Leverage Terhadap Nilai Perusahaan : Moderasi Volatilitas Harga pada Sektor Komoditas - Raka Hanantio Handoko; Rini Tri Hastuti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the effect of profitability, liquidity, and leverage on firm value, with commodity price volatility serving as a moderating variable, in commodity sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample consisted of 77 companies selected using the purposive sampling method. Secondary data were analyzed using Moderated Regression Analysis (MRA) with EViews 12. The results indicate that profitability has no significant effect on firm value, liquidity has a positive and significant effect, while leverage has a negative and significant effect on firm value. Commodity price volatility moderates the relationship between profitability and firm value as well as between leverage and firm value, but does not moderate the relationship between liquidity and firm value.